Ethical leadership and employee-organisational outcomes in the hotel industry - A. Tahernejad; Z. Seyed Ghorban; R. N. Raja Ariffin; H. Babaei (South African Journal of Business Management, 2015)
Ethical leadership has been attracting attention of different kinds. While the concept is still in its infancy, contribution from all aspects of business and management is required to examine the cross-sectional, cross-cultural applicability to provide further insights. Attempts have been made to theoretically and empirically examine the relationship between ethical leadership and several outcomes (e.g. job satisfaction, organisational commitment), however, most of these studies have been conducted in western countries. This calls for further analysis of this particular leadership style to fill the existing gap and enrich the literature. Using 183 samples from middle managers/supervisors in the hotel industry in Malaysia, the present study found that ethical leadership is positively and significantly related to both job satisfaction and organisational commitment among these middle managers, which then resulted in negative turnover and positive organisational citizenship behaviors amongst them. While, contributing significantly to the current literature on ethical leadership in the hospitality industry, this research also provides support for the notion of constructive consequences of leaders becoming role models in their organisations by following ethical standards in their behaviors and decision-making process.
Keywords: 650